Synthesis and herbicidal activities of the O-syn and O-anti benzyl epoxycyclopentyl ethers - Tamogami, S.(Akita Prefectural Univ. (Japan)); Nakayama, K; Noma, M (Journal of Pesticide Science, 2004)
O-syn and O-anti benzyl epoxycyclopentyl ethers were synthesized and their herbicidal activity was investigated. The O-syn isomers were found to be active, and the O-anti isomer was inactive. Thus, benzyl epoxycycopentyl ethers require two oxygens with the syn stereochemistry for herbicidal activity. The O-syn configuration should be considered in addition to the geometrical l,4-relationship to optimize herbicidal activity.